POTENSI JAMUR ENTOMOPAGEN Beauveria bassiana VUILL. UNTUK MENGENDALIKAN ULAT GRAYAK (Spodoptera litura F.) POTENCY OF THE ENTOMOPATHOGENIC FUNGUS Beauveria bassiana VUILL. FOR CONTROLLING ARMYWORM (Spodoptera litura F.) - Wibawanti, Ratri; , Herminanto (Pembangunan Pedesaan, 2010)
A research has been conducted to know the potency of the entomopathogenic fungus Beauveria bassiana for controlling Spodoptera litura on soybean of Slamet variety, the most effective concentration of the fungus for controlling it, and effect of the fungus on the development of S. litura larvae. It was done in the Laboratory of Plant Pests, the Department of Plant Pests and Diseases, Faculty of Agriculture, Jenderal Soedirman University, Purwokerto. The factorial CRD rd th was used with three replicates. The first factor was larval instars, i.e., 3 and 4 instar. The second -1 8 one was concentration of the fungus, i.e., control, B. bassiana of 2 g l aquadest (1.34 x 10 conidia -1 -1 8 -1 -1 8 -1 -1 8 -1 -1 l ), 4 g l (2.58 x 10 conidia l ), 6 g l (4.17 x 10 conidia l ), 8 g l (5.30 x 10 conidia l ), 10 g l 8 -1 -1 8 -1 (6.69 x 10 conidia l ), and 12 g l (8.12 x 10 conidia l ). Result of the research performed that B. bassiana was potency for controlling S. litura on soybean of Slamet variety. The highest -1 th concentration (12 g l ) of the fungus killed 56.67% of the 4 larvae instar. This fungus could lenghten development time of the larvae.